2015
DOI: 10.1016/j.jlumin.2014.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Scintillation properties of CdF2 crystal

Abstract: CdF 2 single crystal was prepared by Tokuyama Corp. with the -PD method to investigate Auger free luminescence of this material. From optical transmittance spectrum, bandgap wavelength was around 280 nm. In X-ray induced radioluminescence spectrum, emission lines appeared around 350 nm and 420 nm. Excitation wavelength was investigated and excitation peak was around 250 nm. Photoluminescence and scintillation decay times were evaluated and decay time was few ns. Temperature dependence of X-ray induced radiolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…2) with components at λ = 295 nm, 320 nm and 420 nm2646 and a much smaller component is detected in visible (λ = 650 nm), as it was found in the earlier published reports.…”
Section: Discussionsupporting
confidence: 79%
“…2) with components at λ = 295 nm, 320 nm and 420 nm2646 and a much smaller component is detected in visible (λ = 650 nm), as it was found in the earlier published reports.…”
Section: Discussionsupporting
confidence: 79%
“…Conventionally, it was considered that they have no temperature dependence concerning the scintillation light yield; 57) but we recently revealed that Auger free luminescence materials also shows a temperature dependence. 58) …”
Section: Recent Randd Progress Of Scintillatorsmentioning
confidence: 99%
“…Meanwhile the hygroscopic nature of such halide crystals is a practical disadvantage, which requires special handling and packaging techniques. Our group has previously studied some non-and low-hygroscopic halide crystalline scintillators [7][8][9][10][11]. The present study focuses on the CsCaCl 3 crystal as a host material, which is congruently melted at 910 °C and is minimally hygroscopic [12,13].…”
Section: Introductionmentioning
confidence: 99%